Comparison of myocardial perfusion study and invasive hemodynamic measurement of the significance of non-infarct-related residual stenoses in ST elevation myocardial infarction patients - Vacha, Jan; Spacek, Miloslav; Kaminek, Milan; Hutyra, Martin; Nykl, Radomir; Sluka, Martin; Taborsky, Milos (Biomedical papers, 2024)
Background. Nearly 50% of ST elevation myocardial infarction (STEMI) patients have multivessel coronary artery disease. The optimal selection of non-culprit lesions for complete revascularization is a matter of current debate. Little is known about the predictive value of myocardial perfusion study (MPS) in this scenario.Methods. We enrolled 49 STEMI patients (61.5 extpm 10.3 years) with at least one major non-culprit lesion (50-90%) other than left main coronary artery lesions. Overall 63 non-infarct- related artery (IRA) stenoses (65.2 extpm 11.9%) were recommended for further evaluation using Fractional Flow Reserve (FFR) measurement as is standard in our institution. Prior to FFR, all patients were scheduled for non-invasive MPS using single-photon emission computed tomography (SPECT). Both FFR and MPS were performed 4-8 weeks after STEMI with MPS preceding FFR within no more than 48 hours. An FFR value of ≤0.80 was considered significant and guided the final revascularization strategy. The results of MPS were correlated to FFR as well as to the clinical and angiographic characteristics of both culprit and non-infarct-related lesions.Results. Based on FFR, 30 out of 63 stenoses (47.6%) in 27 patients were considered hemodynamically significant (FFR 0.69 extpm 0.08, range 0.51-0.79) compared to residual 33 stenoses considered negative (FFR 0.87 extpm 0.04, range 0.81-0.96). The MPS revealed abnormal myocardium (23.6% average, range 5-56%) in 21 patients (42.8%). Among those patients, only 9 showed the evidence of ischemic myocardium (average 10.8%, range 4-18%) with low sensitivity of MPS in predicting positive FFR. Besides that, higher proportion of patients (71.4% vs. 42.9%, P=0.047) with overall lower FFR values (0.73 vs. 0.80, P=0.014, resp.) in non-IRAs as well as higher proportion of patients with more severely compromised flow in IRAs (P=0.048) during STEMI had MPS-detected abnormal myocardium.Conclusion. In STEMI patients with multivessel coronary artery disease, we observed rather weak correlation between MPS using SPECT and invasive hemodynamic measurement using FFR in ischemia detection.
Keywords: atherosclerosis; acute ST elevation myocardial infarction (STEMI); multivessel coronary artery disease (CAD); infarct related artery (IRA); complete revascularization; coronary flow; fractional flow reserve (FFR)